2015
DOI: 10.1016/j.proeng.2015.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Conception of a Simulation Model for Business Continuity Management Against Food Supply Chain Disruptions

Abstract: This paper focusses on robust decision-making in disaster response where pre-existing logistical structures have not been destructed yet but where a great risk of delayed consequences exists if the functioning of these structures is not strengthened. Responsible decision-makers are companies as operators of the logistical structures themselves, particularly those whose businesses refer to the critical infrastructure sectors food, water, health care, and energy. This paper outlines a conception of a simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Next, several studies implemented technologies because they found useful outcomes [38,43,45,53,94,[109][110][111][112][113][114]. Efficiency was pointed out in developing IT for DRM as well [39,79,82,85,115,116]. These important issues of PU were the most founded factors in the selected research articles.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
“…Next, several studies implemented technologies because they found useful outcomes [38,43,45,53,94,[109][110][111][112][113][114]. Efficiency was pointed out in developing IT for DRM as well [39,79,82,85,115,116]. These important issues of PU were the most founded factors in the selected research articles.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
“…Mousavi et al (2019) used model-based system engineering to create conceptual models for order management process simulations within complex semiconductor manufacturing SCP systems. Finally, Schätter and Morelli (2021) presented a method for combining BPS and supply chain risk management to develop a resilient supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The combination of business process simulation (BPS) and supply chain planning (SCP) Jain and Ervin (2005) To assess how well systems and business processes have been improved in a supply chain for distribution and logistics An and Jeng (2005) To present ideas and heuristics to generate supply chain system dynamics models Van Der Vorst et al (2009) To analyze the impact of food quality change and environmental load in redesigning food supply chains Zhang et al (2010) To provide a way for employing integration and coordination across the entire supply chain to reengineer the order fulfillment process (OFP) and sustain supply chain management Wu et al (2011) To analyze the enterprise distribution business process and use the simulation data to improve the optimization model Wang et al (2011) To determine the value of collaboration in the supply chain through enhancing business processes from the standpoint of business simulation Windisch et al (2013) To provide a methodological framework for the detailed examination of the composition and operation of supply chains for forest fuels in different operational contexts Mousavi et al (2019) To develop conceptual models for supply chain planning systems that simulate the order management process in sophisticated semiconductor manufacturing Schätter and Morelli (2021) To provide a resilient supply chain in the supply chain risk management field…”
Section: Humanitarian Supply Chain Planningmentioning
confidence: 99%
“…Under this approach, operational resilience is achieved by identifying critical processes and resources, and consequently by protecting said resources and ensuring the business continuity of said processes [19]. Other elaborations providing a more in-depth insight included studies on the simulation and use of different scenarios in decision making [20,41]. The summary of this group creates a conclusion that the inclusion of risk and crisis management strategies in business continuity management facilitates better resilience of businesses to the effects of negative phenomena and incidents [24].…”
Section: Systematization Of the Relevant Literaturementioning
confidence: 99%